An investigation into the structure and process of forgiveness following gross human rights violations - Adonis, Cyril Kenneth (Rhodes University, Faculty of Humanities, Department of Psychology, 1999)
This study focuses on the structure and process of forgiveness as experienced by individuals, from the East London and surrounding areas, who either suffered gross human rights violations or who are related to someone who suffered gross human rights violations during the Apartheid era. Those who participated in the study testified at the Truth and Reconciliation Commission and expressed forgiveness towards the perpetrators of the violations. The aims of the study were to reveal: the participants' structure cif forgiveness, i.e. how they define forgiveness; the process of forgiveness, i.e. the changes that took place from the time of the violation up until the participants forgave the perpetrators: and, the relation. if any. between the participants' structure and process of forgiveness. It is argued that mainstream Psychology has neglected to study forgiveness because the subject matter is incompatible with the natural scientific method. For this reason, the study was approached from a hermeneutical paradigm. This was motivated by its ability to explicate the meaning and content of phenomena. Unstructured qualitative interviews were conducted with the participants. Data was analyzed using a multi-layered process of progressively deeper interpretation, employing a reading guide technique. Results indicated that authentic forgiveness is an unconditional commitment on the part of victims and survivors to relate positively towards the perpetrators. The relationship should include non-bitterness, non-vengeance, unconditional love and respect for their human rights. Another significant dimension of the structure of forgiveness is the fact that the desire for the truth is not abandoned although forgiveness has taken place. Forgiveness also does not take away the effects of the violation. This means that one does not forget although forgiveness has been granted. Results further indicate that the forgiveness process is highly complex, individualized and not instantaneous. The individuals have to deal with various intrapersonal conflicts and anxieties as a result of the violation, before forgiveness is explored as an option, and before they can finally forgive. Significant interrelations between the structure and process of forgiveness were also identified.
Keywords: Human rights; Forgiveness -- South Africa; South Africa. Truth and Reconciliation Commission; Amnesty -- South Africa; Reconciliation